2011
DOI: 10.1111/j.1523-5378.2011.00863.x
|View full text |Cite
|
Sign up to set email alerts
|

13C-Urea Breath Test for the Diagnosis of Helicobacter pylori Infection in Children: A Systematic Review and Meta-Analysis

Abstract: The (13) C-UBT performance meta-analyses showed 1, good accuracy in all ages combined (sensitivity 95.9%, specificity 95.7%, LR+ 17.4, LR- 0.06, diagnostic odds ratio (DOR) 424.9), 2, high accuracy in children >6 years (sensitivity 96.6%, specificity 97.7%, LR+ 42.6, LR- 0.04, DOR 1042.7), 3, greater variability in accuracy estimates and on average a few percentage points lower, particularly specificity, in children ≤6 years (sensitivity 95%, specificity 93.5%, LR+ 11.7, LR- 0.12, DOR 224.8). Therefore, the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 72 publications
1
101
0
7
Order By: Relevance
“…In the current study 60 children aged 7-17 years were included which had difference compared to Kawakami et al (17) and Machado et al study (23) . In 2011, a systematic review and meta-analysis by Leal et al declared sensitivity of 95.9% and specificity 95.7% for all age groups (20) . The authors insisted that all results of UBT have to be adjusted for cutoff value, pretest meal, and urea dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study 60 children aged 7-17 years were included which had difference compared to Kawakami et al (17) and Machado et al study (23) . In 2011, a systematic review and meta-analysis by Leal et al declared sensitivity of 95.9% and specificity 95.7% for all age groups (20) . The authors insisted that all results of UBT have to be adjusted for cutoff value, pretest meal, and urea dose.…”
Section: Discussionmentioning
confidence: 99%
“…The authors insisted that all results of UBT have to be adjusted for cutoff value, pretest meal, and urea dose. By accommodating these factors, the accuracy of the test can be improved (20) . UBT has a advantage over the endoscopy for evaluation of H. pylori, because it is non invasive and there is no sampling error associated with endoscopic biopsy because of patchy infiltration of H. pylori (24) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the urea breath test and the HpSA test are recommended for diagnosis in the guidelines regarding pediatric H. pylori infection [25]. Previously conducted studies reported that the urea breath test had a sensitivity and specificity in the range of 95.7–96.6 and 95.2–97.7%, respectively, and that the HpSA test had a sensitivity and specificity in the range of 88.9–96.0 and 94.0–96.8% respectively [23, 26-29]. The serologic test for H. pylori infection can be easily performed in epidemiologic studies using stored sera.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis, Leal et al [52] confirmed that the 13 C UBT is less accurate for the diagnosis of H. pylori infection in young children.…”
Section: Urea Breath Testmentioning
confidence: 99%